Optimizing Organizational Performance through E-Government Implementation: The Moderating Effect of Learning Organizations - Dwi Ferdiyatmoko Cahya Kumoro (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Public sector organizations face increasing pressure to improve service quality, efficiency, and accountability through digital transformation. This study analyzes the effect of e-government implementation on organizational performance and examines the role of learning organizations as a moderating variable. E-government is a key strategy to improve public service effectiveness, work efficiency, transparency, and accountability. Its success depends on the organization’s ability to foster an adaptive and innovative learning environment. Using a quantitative survey of public sector institutions and Structural Equation Modeling (SEM), the study finds that e-government implementation has a positive but insignificant effect on organizational performance. Learning organizations, however, significantly improve performance. When acting as a moderator, learning organizations weaken the relationship between e-government and performance and show no significant effect. This indicates that organizational learning has not been fully integrated into e-government efforts, limiting its impact on digital transformation effectiveness. The study emphasizes that strengthening organizational learning capacity and aligning it with e-government strategies is essential to enhancing performance.